Obstetric profile during and before COVID 19 period pandemic at a teaching hospital in Eastern Nepal - Bhansakarya, Rakina; Baral, Gehanath; Subedi, Shanti; Ghimire, Sita; Shrestha, Prajmi; Chaudhary, Amar Nath (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To compare fetomaternal outcomes among pregnant patients in COVID and non-COVID period in tertiary centre in eastern Nepal.Methods: All women who delivered at Nobel Medical College Teaching Hospital during non- COVID period between April to June 2019 and COVID period between April to June 2020 were compared. Data were collected from medical records.Results: Significant number of women had cesarean deliveries in COVID period (36.5% vs 32.6%). There were no significant differences in period of gestation at the time of delivery, birth weight of baby, intrauterine fetal death and neonatal intensive care unit admission as well as no difference in obstetric outcomes, labor complications, maternal intensive care unit stay, near miss and peripartum hysterectomy. Conclusion: There were more cesarean sections, vaginal birth after cesarean section and vaginal breech delivery in COVID period and no other significant differences in maternal and fetal outcomes during COVID period and Non-COVID period.